Spatial differentiation and influencing factors of green finance development level in China - Zhou, Yuanxiang; Liu, Huayan; Wang, Jingxuan; Yang, Hongrui; Liu, Ziyun; Peng, Gang (Frontiers in Environmental Science, 2022)
The entropy method measures the development level of green finance in 30 provinces and cities in China, and the spatial analysis method is used to describe the difference. Spatial pattern of the development level of green finance in China and empirically analyze the influencing factors of the development level of green finance. The results of the spatial econometric model show that the absolute difference in the development level of China's green finance shows an overall increasing trend, and the relative difference shows a downward trend year by year.The level of financial development and environmental governance promote the development of green finance, while the level of economic growth and energy consumption inhibit the development of green finance. On this basis, I put forward countermeasures and suggestions to promote the development of green finance in China, starting with strengthening government functions and adjusting industrial structures based on economic growth.